Creative advances in groupwork - Chesner, Anna; Hahn, Herb (Jessica Kingsley, 2002)
Groupwork is an evolving area, and the authors of this book seek to encourage and inspire practitioners into thinking and developing new methods. Subjects covered include group therapy and spirituality, experimental groups, merging and splitting, playback theatre and sociodramas.